Problematika dalam Menghafal Al-Qur’an di SMP IT Nurul Ilmi Islamic Boarding School - Yenni Rahman; Yayang Virahmawaty (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2020)
What a glory it is for the one who is given by God the ability to memorize the Qur'an. They will be glorified by God in the form of intercession, a blessed position, a great reward, and with a noble angel and of course the chosen one who is entrusted by God as the guardian of revelation (The Qur'an). When memorizing the Qur'an there must be problems from the memorization of the Qur'an, whether it is problems internally (from within) or externally (from outside), research is designed with qualitative research design. The technique of collecting researchers acts as an active participant. Research location at SMP IT Nurul Ilmi Koto Kociak.From the results of this study found that (a) Internal problems in memorization in SMP IT Nurul Ilmi is the lack of self-management terhdap lazy traits, and set a good time to play and to memorize. (b) External problems in memorizing the Qur'an at SMP IT Nurul Ilmi are the influence of friends of different characters leads to laziness, lack of tahfidz teachers, and appreciation from schools that still need to be improved.(c) Efforts can be made to overcome internal problems, fight with motivation, multiply memorization. Ask for prayers and support from the family. And efforts to overcome externally by not choosing a friend or partner, tahfidz teachers are given training, looking for a comfortable place when memorizing.